1999
DOI: 10.1029/1999wr900097
|View full text |Cite
|
Sign up to set email alerts
|

Field test of high molecular weight alcohol flushing for subsurface nonaqueous phase liquid remediation

Abstract: Abstract. A pilot scale field test of non-aqueous phase liquid (NAPL) removal using high molecular weight alcohols was conducted at Operable Unit 1, Hill Air Force Base, Utah. Petroleum hydrocarbons and spent solvents were disposed of in chemical disposal pits at this site, and these materials are now present in the subsurface in the form of a light nonaqueous phase liquid (LNAPL). This LNAPL is a complex mixture of aromatic and aliphatic hydrocarbons, chlorinated solvents, and other compounds. The field exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…Chemical agents have been utilized in laboratory, intermediate, and field-scale experiments including cosolvents Rao et al 1985;USEPA 1985;Boyd and Farely 1992;Brandes and Farley 1993;Peters and Luthy 1993;Augustijn et al 1994;Imhoff et al 1995;Roy et al 1995;Wang and Brusseau 1995a;Wood 1995;Rao et al 1997;Sillan et al 1998;Falta et al 1999;Jawitz et al 2000;Chawla et al 2001;Brooks et al 2004), surfactants (Abdul et al 1990;Abdul and Gibson 1991;Edwards et al 1991;Fountain et al 1991;Pennel et al 1993;Rouse et al 1993;Brown et al 1994;Shiau et al 1994;Adeel and Luthy 1995;Hasegawa et al 1997;Childs et al 2006), and complexing sugar agents Brusseau 1993, 1995a b;Brusseau et al 1994Brusseau et al , 1997Bizzigotti et al 1997;Wang et al 1998;Brusseau 1998, 1999;Boving et al 1999;Boving and Brusseau 2000;McCray et al 2000;Blanford et al 2001;Tick et al 2003;Carroll and Brusseau 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical agents have been utilized in laboratory, intermediate, and field-scale experiments including cosolvents Rao et al 1985;USEPA 1985;Boyd and Farely 1992;Brandes and Farley 1993;Peters and Luthy 1993;Augustijn et al 1994;Imhoff et al 1995;Roy et al 1995;Wang and Brusseau 1995a;Wood 1995;Rao et al 1997;Sillan et al 1998;Falta et al 1999;Jawitz et al 2000;Chawla et al 2001;Brooks et al 2004), surfactants (Abdul et al 1990;Abdul and Gibson 1991;Edwards et al 1991;Fountain et al 1991;Pennel et al 1993;Rouse et al 1993;Brown et al 1994;Shiau et al 1994;Adeel and Luthy 1995;Hasegawa et al 1997;Childs et al 2006), and complexing sugar agents Brusseau 1993, 1995a b;Brusseau et al 1994Brusseau et al , 1997Bizzigotti et al 1997;Wang et al 1998;Brusseau 1998, 1999;Boving et al 1999;Boving and Brusseau 2000;McCray et al 2000;Blanford et al 2001;Tick et al 2003;Carroll and Brusseau 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Besides conventional methods, there are many innovative treatment approaches available now to remediate sites contaminated with chlorinated solvents. Some techniques rely on zero-valent metals (Gilham & O'Hannesin, 1994), others on microorganisms (Chapelle, 2001), and others are based on destruction (e.g., in situ oxidation by permanganate or peroxide; Huling & Pivetz, 2006), or chemically enhanced flushing with surfactants, cosolvents, or cyclodextrin solution (Boving et al, 1999;Falta et al, 1999;Jawitz et al, 1998;Sabatini et al, 1996). Of these innovative remediation technologies, this study focuses on in situ cyclodextrin-enhanced chemical flushing of a DNAPL source zone in conjunction with ex situ treatment of the postaquifer flushing solution by ultrafiltration (UF).…”
Section: Introductionmentioning
confidence: 98%
“…They also reported an approximate 81% reduction in NAPL saturation based on pre-and post-flushing partitioning interwell tracer tests (PITTs). Falta et al (1999) presented results from a second cosolvent flushing study at Hill AFB wherein the remedial mechanisms were NAPL mobilization and enhanced dissolution. Their test cell was approximately 5 m long by 3 m wide, and the clay confining unit was 9 m below grade.…”
Section: Technology Status: Cosolvent Flushingmentioning
confidence: 99%
“…Two cosolvent flushing demonstrations were conducted at Hill Air Force Base (AFB), Utah in isolated test cells installed in a sand and gravel aquifer contaminated with a multi-component NAPL Sillan et al, 1998a;Falta et al, 1999). Rao et al (1997) demonstrated NAPL remediation by enhanced dissolution.…”
Section: Technology Status: Cosolvent Flushingmentioning
confidence: 99%